Effects of Varying the Acid-Binding Capacity-4 in Diets Utilizing Specialty Soy Products with or without Pharmacological Levels of Zinc on Nursery Pig Performance - Ethan B. Stas; Alan J. Warner; Chad W. Hastad; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 1,057 pigs (PIC TR4 × [Fast LW × PIC L02]; initially 13.7 lb) were used to evaluate the effects of acid-binding capacity-4 (ABC-4) with or without pharmacological levels of Zn on nursery pig performance. At weaning, pigs were allotted to 1 of 4 dietary treatments based on initial weight. There were 22 pigs per pen and 12 replications per treatment. Dietary treatments were arranged in a 2 × 2 factorial consisting of a low and high ABC-4 level with or without pharmacological levels of Zn provided by ZnO. The low ABC-4 diets contained 13.0 and 10.75% novel soy protein concentrate (AX3 Digest; Protekta; Plainfield, IN) in phase 1 and 2, respectively. The high ABC-4 diets contained 15.85 and 13.15% enzymatically treated soybean meal (HP 300; Hamlet Protein; Findlay, OH) in phase 1 and 2, respectively, replacing the soy protein concentrate on an SID Lys basis. The low ABC-4 diets without ZnO were formulated to 150 and 200 meq in phase 1 and 2, respectively. Replacing novel soy protein concentrate with enzymatically treated soybean meal increased the ABC-4 of the diet by approximately 104 to 127 meq/kg. Diets with added ZnO increased the ABC-4 of the diet by approximately 60 to 65 meq/kg. Pigs were fed experimental diets during phase 1 (d 0 to 7) and phase 2 (d 7 to 21). Following phase 2, pigs were placed on a common diet for an additional 21 d (d 21 to 42). During the experimental period, ABC-4 × ZnO interactions were observed (P≤ 0.026) where pigs fed a low ABC-4 diet had improved (P<0.05) ADG and F/G when ZnO was not present, but no differences (P>0.10) were observed based on ABC-4 level when ZnO was added. Overall, there was an ABC-4 × ZnO interaction (P= 0.002) observed where pigs fed a high ABC-4 had increased (P<0.05) removals and mortalities when ZnO was not present, and no differences (P>0.10) due to ABC-4 level were observed when ZnO was added. For economics, there was an ABC-4 × ZnO interaction (P≤ 0.039) where pigs fed low ABC-4 diets had increased (P<0.05) gain value, feed cost, and IOFC when ZnO was not present, and no differences (P>0.10) due to ABC-4 level were observed when ZnO was added. In summary, a low ABC-4 diet can improve growth performance, reduce the instance of removals and mortalities, and improve economics in nursery pigs when ZnO is not present in the diet.
Keywords: acid-binding capacity; soy products; zinc oxide; nursery pig